2023
DOI: 10.1371/journal.pone.0288646
|View full text |Cite
|
Sign up to set email alerts
|

Change in the faunal composition of mosquitoes (Diptera: Culicidae) along a heterogeneous landscape gradient in the Brazilian Amazon

Abstract: This study aimed to evaluate the influence of different anthropic landscape profiles on the diversity and distribution of mosquito species in a rural settlement of the Brazilian Amazon. Eight field collections were conducted at 18 sampling points interspersed throughout 2020–2021. Plastic containers, bamboo internodes, and tires were used as traps to capture immature mosquitoes in three distinct habitats: forest, forest edge, and peridomicile. A total of 15,547 individuals, distributed in 26 species of culicid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…Forest edges, where humans, mosquitoes, and wildlife overlap may serve as a nexus for zoonotic arbovirus exchange 8 . Studies have investigated shifts in mosquito communities [9][10][11][12] and wildlife [13][14][15] from interior forest to forest edge, and then to human-modified landscapes. Despite suggestions that mosquito diversity should peak in edge habitats 10 , where urban and sylvatic species overlap, empirical studies have not consistently found highest diversity at edges 9,10,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Forest edges, where humans, mosquitoes, and wildlife overlap may serve as a nexus for zoonotic arbovirus exchange 8 . Studies have investigated shifts in mosquito communities [9][10][11][12] and wildlife [13][14][15] from interior forest to forest edge, and then to human-modified landscapes. Despite suggestions that mosquito diversity should peak in edge habitats 10 , where urban and sylvatic species overlap, empirical studies have not consistently found highest diversity at edges 9,10,16,17 .…”
Section: Introductionmentioning
confidence: 99%